Implementation of rapid diagnostics with antimicrobial stewardship. Issue 11 (1st November 2016) - Minejima, Emi; Wong-Beringer, Annie
ABSTRACT: Introduction : Antimicrobial stewardship (ASP) is an intervention-based program to improve patient outcomes to infection while limiting spread of resistance and unintended consequences. Many rapid diagnostic tools are now FDA cleared for clinical use, with three evaluated across multiple settings: Matrix Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry, Verigene, and FilmArray. Areas c overed : This review will focus on studies published that evaluated ASP intervention with rapid diagnostic implementation on outcomes of infection. A description of the key ASP personnel, rapid diagnostic notification methods, hours of notification, and scope of ASP intervention is summarized. Expert commentary : It is critical that ASPs continually re-evaluate and evolve with technological advances. Rapid diagnostic tools are powerful in their ability to identify organisms quickly. A trained clinician is needed to evaluate the results and interact with the providers to educate them on result interpretation and optimal antimicrobial selection to maximize treatment success.